The Effect of Quality of the Relationship Between Mothers and Adult Children With Schizophrenia, Autism, or Down Syndrome on Maternal Well-Being: The Mediating Role of Optimism - Greenberg, Jan Steven (2004)
This article investigates the effects of the quality of the relationship between maternal caregivers and their adult child with disabilities on maternal well-being and whether this effect is mediated by dispositional optimism. Mothers caring for an adult child with Down syndrome (n = 126), schizophrenia (n = 292), or autism (n = 102) were surveyed. Mothers of adults with schizophrenia and autism had better psychological well-being when the mother/adult child relationship was positive, but this effect was mediated totally or partially by optimism. For all 3 groups, optimism was related to better mental and physical health. The findings highlight the importance of dispositional optimism, a psychological resource that has been virtually ignored in studies of family caregivers of adults with disabilities.